Piroplasmosis in a badger from Turkey [5] - Simsek, S.; Dumanli, N.; Köro?lu, E. (My University, 2003)
[Abstract Not Available]
Keywords: Animals; Babesia; Babesiosis; Carnivora; Diagnosis, Differential; Turkey; Animalia; Carnivora; Taxidea taxus; Trypanosoma; animal parasitosis; blood sampling; blood smear; Carnivora; letter; nonhuman; parasite identification; parasite virulence; parasitemia; protozoal infection; Trypanosoma; Turkey (republic); wild species